2007
DOI: 10.1103/physreva.76.032325
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic cooling algorithm

Abstract: We introduce a scheme to perform the cooling algorithm, first presented by Boykin et al. in 2002, for an arbitrary number of times on the same set of qbits. We achieve this goal by adding an additional SWAP-gate and a bath contact to the algorithm. This way one qbit may repeatedly be cooled without adding additional qbits to the system. By using a product Liouville space to model the bath contact we calculate the density matrix of the system after a given number of applications of the algorithm.PACS numbers: … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 10 publications
0
27
0
1
Order By: Relevance
“…Recently an algorithm published by Boykin et al [12] has found experimental realization by Baugh et al [13] and its thermodynamic properties where investigated by Rempp et al [14]. Of course, not all qubits [i. e. two level systems (TLS) used for quantum computing] are cooled down this way, some, the so called auxiliary qubits, are heated up as well and thus have to be discarded or coupled to the environment to work again as auxiliaries.…”
mentioning
confidence: 99%
“…Recently an algorithm published by Boykin et al [12] has found experimental realization by Baugh et al [13] and its thermodynamic properties where investigated by Rempp et al [14]. Of course, not all qubits [i. e. two level systems (TLS) used for quantum computing] are cooled down this way, some, the so called auxiliary qubits, are heated up as well and thus have to be discarded or coupled to the environment to work again as auxiliaries.…”
mentioning
confidence: 99%
“…Last but not least, in real life, the reset spins do not relax infinitely faster than the computation spins (see [36][37][38][39][40][41] for viewing AC as a novel type of heat-engine). Let R denote the ratio between the relaxation time of the computation spins and the relaxation time of the reset spins, R = T 1 (comp.…”
Section: Discussionmentioning
confidence: 99%
“…We bypassed Shannon's bound in three different processes. The current optimal control methods (GRAPE), and better ones such as a second order GRAPE [42] and Krotov based optimization [43] could enable various applications of AC in magnetic resonance spectroscopy [13,14,44] and maybe also other potential applications [45][46][47][48][49][50][51][52][53][54]. ln (4) (see [23]), where ε C,eq is the carbons' equilibrium polarization.…”
Section: Discussionmentioning
confidence: 99%